2003
DOI: 10.1111/j.1751-0813.2003.tb12576.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of equine herpesvirus 1 in mares and foals on a large Hunter Valley stud farm in years pre‐and postvaccination

Abstract: Mares are the source of virus from which foals are infected early in life and following analysis of the 2001 data, the difference in the prevalence of EHV-1 antibody-positive foals between 1995 and 2000 was likely to be a reflection of seasonal, nutritional and management factors, rather than the result of vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…Some commercial vaccines have been shown to contribute to protection from EHV-related respiratory disease, neurological disease, and abortion under experimental conditions (2-4). Many reports have described the serological responses of vaccinated horses in the field (5)(6)(7)(8), and vaccine use is considered to be partially responsible for a reduction in the incidence of equine abortion (9)(10)(11)(12). However, the effect of vaccination on the prevalence of respiratory disease induced by EHV-1 and EHV-4 in the field has not been investigated in detail.…”
mentioning
confidence: 99%
“…Some commercial vaccines have been shown to contribute to protection from EHV-related respiratory disease, neurological disease, and abortion under experimental conditions (2-4). Many reports have described the serological responses of vaccinated horses in the field (5)(6)(7)(8), and vaccine use is considered to be partially responsible for a reduction in the incidence of equine abortion (9)(10)(11)(12). However, the effect of vaccination on the prevalence of respiratory disease induced by EHV-1 and EHV-4 in the field has not been investigated in detail.…”
mentioning
confidence: 99%
“…The progression of equine herpesviruses is associated with factors including climate conditions, management activities, population status, transport, and other infections (13). Although EHV-1 and EHV-4 infections are not vector-borne, the cold climate is a stressor for horses that can result in reactivation of latent infections (6,7,12,16). However, the high seroprevalence rates of this region may also be related to the relatively high number of horses per house (≥10 head), new herds in the region, stressful working conditions, climatic extremes, as well as disease spread due to illegal border trade.…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious factors, such as adverse environmental conditions, corticosteroid treatment, stressful work situations, and population structure and density, can increase the reactivation possibility of herpesviruses (6). The contention policy of EHV-1 and EHV-4 infections includes the effective diagnosis, control, and prevention of these diseases (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Australian studies have shown infection of foals in the early weeks of life continues to occur despite vaccination of mares during pregnancy [169,172]. Indeed these studies have shown that the introduction of vaccination has not changed the number of mares seropositive for EHV-1 in the preweaning period and does not appear to have affected the rate of new infection of foals pre-weaning [173]. These studies show that the presence of maternal antibodies alone is not enough to prevent EHV-1 seroconversion associated with EHV infection.…”
Section: Epidemiology and Conclusionmentioning
confidence: 99%